Analisis Timbulan Sampah dan Pengelolaannya di Kelurahan Tabing Banda Gadang Kota Padang - Fitra, Miladil; Awaluddin, Awaluddin; Desman, Akhirul (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2023)
Food waste is the biggest contributor in Indonesia, namely around 40%, wood/twig/leaf waste is 17%, plastic is 16%, paper is 10%, metal is 4%, textile fabric is 3%, glass is 2%, rubber is leather. by 2% and other waste by 6%. Of the waste produced, 66.39% is still landfilled at the Final Processing Site (TPA), 19.62% is unmanaged, and only 14% is processed (compost, biogas, recycled raw materials, recycled creative products, processed by banks waste and other processed, raw materials ), research objectives This is known the average weight of waste generated per person per day and Know how to manage waste on a sub-district scale . The research design used in this research is analytical descriptive using the method of taking and measuring samples of urban waste generation and composition in accordance with SNI 19-3964-1994 , population is House stairs in the village Tabiang banda gadang whereas sample emergence rubbish done in a way randomize appropriate strata with formula SNI 19-3964-1994 found 38 houses stairs , collection and analysis data using instruments/forms and measuring instruments in the form of scales in accordance with SNI 19-3964-1994 . From the research results, the following results were obtained for organic waste : 0.208 Kg/Org/Hr (56%) , Inorganic: 0.128 Kg/Org/Hr (35%) , residue and B3: 0.033 Kg/Org/Hr (9 %) total 0.369 Kg/Org/Hr , this result is the same as the amount of waste generation based on SNI 19-3983-1995, namely in permanent houses with a weight of 0.350-0.400 kg/org/hr. The recommended waste management method is as follows ( Organic waste can be processed using a composter and biopore and inorganic waste can be deposited into a waste bank. Therefore, it is recommended that the sub-district establish a waste bank so that inorganic waste can be reduced.